SOCIAL FORESTRY AND ENVIRONMENTAL PROTECTION: सामाजिक वानिकी एवं पर्यावरण संरक्षण - Singh Thakur, Devendra (International Journal of Research -GRANTHAALAYAH, 2015)
Environment means the environment around us which directly and indirectly affects our lifestyle. In the theoretical and practical form the management of forests and proper use of their products is called forestry. According to the field of work, there are many types of forestry such as agricultural forestry, garden forestry, rural forestry, urban forestry, social forestry. Afforestation done for the purpose of social service is called social forestry. Social forestry performs an important task of meeting the basic needs of the society as well as maintaining the environmental balance. Social forestry has affected human life and the environment. In my research paper, the meaning, necessity, purpose, functions and utility of social forestry has been highlighted and how much social forestry has affected human life. In present times, an attempt has been made to convey the importance of social forestry. Through this research work people will be able to understand the need and importance of social forestry. पर्यावरण अर्थात हमारे चारो ओर का वातावरण जो प्रत्यक्ष और अप्रत्यक्ष रूप से हमारी जीवनषैली को प्रभावित करता है। सैद्धांतिक एवं व्यावहारिक रूप में वनो की संरचना प्रबंध तथा उनके उत्पादो का उचित उपयोग वानिकी कहलाता है। कार्यदृष्टि के क्षेत्र अनुसार वानिकी के अनेक प्रकार है जैसे कृषि वानिकी, उद्यान वानिकी, ग्रामीण वानिकी, नगरीय वानिकी , सामाजिक वानिकी। सामाजिक सेवा के उद्देष्य से किया गया वनीकरण सामाजिक वानिकी कहलाता है। सामाजिक वानिकी समाज की मुलभूत आवष्यकताओं की पूर्ति करने के साथ साथ पर्यावरण संतुलन को बनाये रखने का महत्वपूर्ण कार्य करती है। सामाजिक वानिकी ने मानवजीवन और पर्यावरण को प्रभावित किया है। मेरे षोध पत्र में सामाजिक वानिकी का अर्थ, आवष्यकता, उसके उद्देष्यो, कार्यो और उसकी उपयोगिता पर प्रकाष डाला गया है तथा सामाजिक वानिकी ने मानव जन जीवन को कितना प्रभावित किया है, को बताया गया है। वर्तमान समय में हमें सामाजिक वानिकी की कितनी आवष्यकता है को महत्व को प्रतिपादित करने का प्रयास किया गया है। इस षोध कार्य के जरिए लोग सामाजिक वानिकी की आवष्यकता और महत्व को भलिभांति समझ सकेगे।